PMO-084 The evolution of a virtual peg assessment team: activity and complications. (28th May 2012) - Donnelly, S C; Sweis, R; Sayer, V; Bensaid, L; Hayee, B
Abstract : Introduction: Patients referred for percutaneous Endoscopic Gastrostomy (PEG) insertion often have multiple co-morbidities which do not improve with PEG feeding and lead to significant post-procedure complications. Pre-assessment of patients for PEG insertion improves morbidity and mortality, but is often time-consuming and labour-intensive. An electronic patient record (EPR) could facilitate assessment of patients and multi-disciplinary communication, while a detailed referral form could speed up the information gathering and assessment process. Starting in February 2011 in our Trust, patients referred for PEG were formally pre-assessed at the bedside by a Consultant Gastroenterologist and Nurse Endoscopist. In June 2011 a new electronic referral form was introduced. As a result of the improvements from February to May, a "virtual" assessment team including a Senior Dietician, Speech and Language Therapist, Elderly Care and Palliative Care physician was convened. The referral form was sent by secure email to the team and a virtual discussion took place with formal MDT meeting held when deemed prudent by consensus. Bedside assessment could then be restricted an assessment of fitness for the endoscopic procedure. Data were collected prospectively throughout the year and compared to practice in the preceding 12 months. Methods: Retrospective casenote analysis was conducted using the EPR and Endoscopy databases (Endosoft ® ) to include all PEG insertions performed. Prospective data collection were possible for all cases undergoing formal and virtual assessment. Results: In 2010, 96 PEG insertions were performed (median 6 per month), compared to 49 within the "formal" and "virtual" team periods (median 2 per month, p<0.005). Patients did not differ significantly by age or gender. 30d mortality was 9/96 (9.4%) in 2010 and 2/49 in 2011 (4.1%; p=0.33). Rates of infection, aspiration pneumonia, buried bumper syndrome and other complications fell significantly (p<0.001). The number of referrals not leading to insertion fell significantly between the formal and virtual assessment periods (p<0.01) with no PEGs inserted in June and July. In addition, the time from referral to insertion increased significantly across these periods (p<0.01). In the later part of 2011 an increase in referrals and appropriate insertions was observed—without a concomitant rise in complications. Conclusion: Introduction of a "virtual" team for PEG assessment reduced the number of procedures required (freeing time for other endoscopic procedures), and post-insertion complications. There was a non-significant trend for improved 30-day mortality. A "minimal input" approach to PEG assessment based on a detailed referral form is therefore feasible, safe and associated with significantly reduced rates of post-procedure morbidity. Competing interests: None declared.